Disseminated histoplasmosis associated with acquired hemophagocytic lymphohistiocytosis - Rajput, Ashish (Clin Case Rep, 2015)
Hemophagocytic lymphohistiocytosis (HLH) is a potentially life-threatening clinical syndrome caused by uncontrolled activation of lymphocytes and histiocytes resulting in high levels of cytokines. Acquired HLH occurs in autoimmune, inflammatory, infectious, and immunosuppressive disorders. Prompt identification and treatment of an underlying triggering cause improves clinical outcome.